Consumer Protection Regarding the Circulation of Non-SNI Certified Electronic Goods from the Perspective of Maqashid Sharia: A Case Study of an Electronics Store in Medan Denai District - Andri Siregar; Abd Rahman Harahap (Warmadewa Press, 2024)
This research aims to examine the enforcement of SNI (Standar Nasional Indonesia) certification for electronic products in the Medan Denai District of Medan City and to evaluate the accountability of electronic store operators concerning consumer protection under both civil and criminal law. The significance of this study lies in its exploration of the intersection between legal frameworks, consumer rights, and public safety, offering a nuanced understanding of how these elements interact in a localized setting. By focusing on the Medan Denai District, the research not only highlights the specific challenges and dynamics faced in ensuring compliance with SNI standards but also reflects broader national concerns. The incorporation of Maqashid Al-Syari'ah, an Islamic jurisprudential principle, is crucial as it frames the discussion within a moral and ethical context. Maqashid Al-Syari'ah, which aims to protect fundamental human interests such as religion, life, intellect, lineage, and property, provides a unique lens through which consumer protection can be viewed. This perspective emphasizes that ensuring product safety and adherence to standards transcends mere legal obligations, embodying a deeper commitment to fulfilling religious and moral duties. The focus on Medan Denai District as a case study is essential because it offers a tangible example of how these principles are applied in practice, revealing both the successes and limitations of current enforcement mechanisms. This research, therefore, contributes valuable insights into how consumer protection can be enhanced by aligning legal and ethical standards, ultimately promoting societal well-being.